2016
DOI: 10.1016/j.midw.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

‘We make them feel special’: The experiences of voluntary sector workers supporting asylum seeking and refugee women during pregnancy and early motherhood

Abstract: and Downe, Soo (2015) 'We make them feel special': The experiences of voluntary sector workers supporting asylum seeking and refugee women during pregnancy and early motherhood. Midwifery . ISSN 02666138It is advisable to refer to the publisher's version if you intend to cite from the work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 24 publications
2
23
0
1
Order By: Relevance
“…Of interest, the participants did not refer to women’s demographic characteristics as health determinants, but instead to how acculturation, assimilation, or integration [56], described as closely related to the length of stay in the new country, were crucial to these women to navigate both the social system and the health care system, a finding already reported [57]. In line with previous research, it seems that the health care professionals perceive the challenges migrant women go through, but at the same time, justify or reinforce the rules imposed by the health care system [58]. …”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Of interest, the participants did not refer to women’s demographic characteristics as health determinants, but instead to how acculturation, assimilation, or integration [56], described as closely related to the length of stay in the new country, were crucial to these women to navigate both the social system and the health care system, a finding already reported [57]. In line with previous research, it seems that the health care professionals perceive the challenges migrant women go through, but at the same time, justify or reinforce the rules imposed by the health care system [58]. …”
Section: Discussionsupporting
confidence: 67%
“…Our study unveils that more efforts are needed to sensitise health care professionals to be more responsive to the maternity care needs and concerns of migrant women. Although the underlying reason may be that colonial values ruling marginalisation are largely entrenched in the health care system [58]; as for today, it seems that as portrayed by Molière in the The Doctor in Spite of Himself more than 400 years ago, health care professionals have a power associated with their status that they can use to either ‘dictate health’ or provide culturally safe health care services. The question that still remains unanswered is how aware are health care professionals of the power they have in their hands.…”
Section: Resultsmentioning
confidence: 99%
“…This supports findings from McLeish and Redshaw’s [ 54 ] study, which found that being supported by trained volunteers who remained outside the ‘social circle’ provided relief, promoted trust, rebuilt self-esteem, and increased empowerment – ultimately, facilitating recent migrant women to honestly share their feeling. Balaam et al’s [ 38 ] findings also highlighted this phenomenon, as their study illustrated how volunteer workers assisted in identifying and providing alternative routes into the healthcare system, in order to ensure that migrant women receive the care they needed. Whilst previous findings referred to migrant women living as refugees and asylum-seekers, combined with the results of the present study it could be argued that healthcare organizations could improve their approach by learning from, and cooperating with NGOs who cater to migrant women, both registered and undocumented.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study found that receptionists at healthcare facilities have refused access to women who presented without residency status, and women have also been required to pay in advance when seeking abortions [ 25 ]. Midwives have reported experiencing ethical dilemmas due to their limited ability to provide continuous care to women living as asylum-seekers, refugees, and undocumented migrants [ 34 , 38 , 39 ]. Volunteer healthcare staff have reported being concerned about healthcare professionals’ prejudicial attitudes toward migrant women, and a need for NGO assistance in bridging the gap between the inherent marginalized position these women hold and the need for adequately supporting them in perinatal care has been raised in previous findings [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation